ASAN LUIS POTOSIERGILLUS NIGER COMO INDICE DEL CONTENIDO EN POTASIO Y EN SODIO DE LOS SUELOS - TAMAYO, M R; SANCHEZ MARROQUIN, AY (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1948)
Expts of infecting Boophilus annulatus, Amblyomma cajennense, Cimex lectularius and Ctenocephalides felis with Brucella were performed All of the ectoparasites studied were susceptible to infection with the 3 species, B melitensis, B abortus and B su
AN ESC NAC CIENC BIOL
Keywords: ASPERGILLUS NIGER, INDICE, CONTENIDO, POTASIO, SODIO, SUELOS; CIENCIAS DE LA VIDA; BIOLOGIA CELULAR; CULTIVO CELULAR